Crazy Quilts : A Beginner's Guide - Pillsbury, Betty Fikes, 1962- (Book collections on Project MUSE., 2016)
This definitive, meticulously illustrated how-to book is far more expansive than previous guides. Pillsbury-a master of the form-shows us why crazy quilting belongs firmly in the category of fine art and serves as an inspiring primer for beginners.